PENGEMBANGAN MATERI MENINGKATKAN KUALITAS INTERAKSI DALAM KELUARGA (ANAK & ORANGTUA) - Dwi Herri Santoso; Raja Arlizon; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The existence of a child's behavior that we can see like cool and less responsive to parents well, the principally it’s happend because the teenagers are at the phase of conflict storm and stress, i thing they prefer the prejudices and emotions at anyone and the parents themselves, for them, the right thing just from theirs. Therefore, the researchers to develop an expected material that can be used by counseling teachers to give to students. This material is prepared using methods of research and development (R & D) The research to 1) To improve material of the quality interaction in the family. 2) To determine the quality of material produced. This material is validated by the supervisor 1&2, counselor, as well as 19 students. This material is tested to the student with the allocation of 3-hour lessons (3 x 45 '). This material consists of the role and functions of the family, the theories of approach in communication, the characteristics of quality communication in family, factors that affect the quality of the interaction and how to create a quality of communication. The results showed that the material produced in the category